Development of spatial perception in high school with GeoGebra - Budai, László (Teaching Mathematics and Computer Science, 2013)
In everyday life, on numerous occasions we need to project 3D space onto a plane in order to activate our spatial perception. While our ability in this area can be improved, and considering several national and international research results, the development is even necessary on all levels of education. GeoGebra, as a supplement to previously used tools, has proven to be very useful respective to the development. We have many possibilities to display spatial elements in GeoGebra and to apply such kind of worksheets among 15-18 year old students. I show the results of the 2011/2012 school years connected to the development of spatial perception and the results of an input case survey, which also justifies the need for development.